An Implementation of a Single Board Computer as a Home Vital Sign Monitoring System Using a Raspberry-Pi - Susana, Ernia; Handayani, Indah Nursyamsi; Komarudin, Agus (Universitas Indonesia, 2023)
Health monitoring and related technologies are a growing area of research. The embedded technology enables designing and manufacturing a single board computer (SBC) based vital signs monitoring system prototype. This study aims to develop and test an equipped with a monitor of vital signs, including electrocardiogram, heart rate (HR), respiratory rate (RR), and body temperature. The results showed that the prototype could work well, all parameters could be displayed on the 7